2008
DOI: 10.1002/elps.200700725
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturizing free‐flow electrophoresis – a critical review

Abstract: Free-flow electrophoresis (FFE) separation methods have been developed and investigated for around 50 years and have been applied not only to many types of analytes for various biomedical applications, but also for the separation of inorganic and organic substances. Its continuous sample preparation and mild separation conditions make it also interesting for online monitoring and detection applications. Since 1994 several microfluidic, miniaturized FFE devices were developed and experimentally characterized. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
175
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 49 publications
0
175
0
3
Order By: Relevance
“…In all studies, proteins primarily involved in translation, energy metabolism, transport processes and the stress response were most abundant. Penicillium chrysogenum, the microorganism industrially used for the production of penicillin, is another example of filamentous fungus whose genome sequence has been recently released (van den Berg et al, 2008). In this specific case, a first study was reported about the intracellular proteome reference map (Jami et al, 2010a).…”
Section: Intracellular Reference Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all studies, proteins primarily involved in translation, energy metabolism, transport processes and the stress response were most abundant. Penicillium chrysogenum, the microorganism industrially used for the production of penicillin, is another example of filamentous fungus whose genome sequence has been recently released (van den Berg et al, 2008). In this specific case, a first study was reported about the intracellular proteome reference map (Jami et al, 2010a).…”
Section: Intracellular Reference Mapsmentioning
confidence: 99%
“…In spite of its popularity, the time consumption (2-3 hours) of the process and batch enzymes variability are cons of this method. Secondly, different methods can be used for debris elimination as filtration; low-speed centrifugation; differential detergent fractionation; centrifugal elutriation; ultracentrifugation (linear or density gradients); immunomagnetic separation, which has been used for organelle isolation (mitochondria vacuoles, microbodies, endosomes, vesicles) in other eukaryotes; or miniaturized free-flow electrophoresis (FFE) (Kohlheyer et al 2008, Ferreira de Oliveira & de Graaff, 2011. A large number of diseases and developmental abnormalities result from mitochondrial functions.…”
Section: Organelle Isolation and Enrichment For Proteome Analysismentioning
confidence: 99%
“…Compared with other separation techniques on a microchip, it has shown great advantages as a continuous separation method, which requires less buffers and samples, simplifies the liquid manifold and improves the impact of Joule heat on electrophoresis. 3 Many kinds of modes can be used on the μFFE chip. 4 Among them, free-flow zone electrophoresis and free-flow isoelectric focusing have recently gained much attention and progress.…”
Section: Introductionmentioning
confidence: 99%
“…Free-flow electrophoresis (FFE) is a common separation technique that has been in use since the 1960's and applied to microfluidic since 1994 [37]. Like CE, FFE uses an electric field to aid in the separation of solutes from each other in an electrolytic buffer solution.…”
Section: A5 Free Flow Electrophoresis (Microfluidic)mentioning
confidence: 99%
“…This method of FFE uses buffers with a constant pH and conductivity to separate different solutes based on their mobility, which is determined by their size-to-charge ratio. Even though CE is primarily used for analysis of analytes and FFZE is used for analyte separations, there is a direct correlation between the operation of the two [37]. For information concerning the comparison of the underlying theory of both techniques, please refer to Kasicka's paper on this topic [38].…”
Section: A5 Free Flow Electrophoresis (Microfluidic)mentioning
confidence: 99%